Estimasi Koreksi Relativistik pada Efisiensi Mesin Carnot dalam Kerangka Non-Inersia - Achmad, Arifin; Muflihatun; Pratiwi, Sulistiyani Hayu (UNIB Press, 2025)
This paper investigates relativistic corrections to the efficiency of Carnot engines in non-inertial frames, focusing on massive objects such as neutron stars and black holes. The results of this study show that, in non-inertial frames, the local temperature and the efficiency of Carnot engines are influenced by rotation and linear acceleration. Using a relativistic approach, it is found that the efficiency correction depends on the acceleration and angular velocity parameters. Simulation results indicate that relativistic corrections become significant under extreme conditions, such as rapidly rotating neutron stars of about 10-4 to 10-3 or in strong gravitational fields around black holes of about O (1). This paper does not examine in detail the mass distribution, magnetic field effects on rotating neutron stars, or quantum effects on black holes. Instead, it focuses on estimating the Tolman temperature correction for non-inertial frames.